The virtual model method in the metrological provision of automated design and control - Становский, Александр Леонидович; Бовнегра, Любовь Витальевна; Шихирева, Юлия Владимировна; Шмараев, Александр Васильевич (Eastern-European Journal of Enterprise Technologies, 2015)
For the metrological provision of design and control, involving processing intermediate measurement results in the form of images, existing compression methods of the latter are not suitable. This is caused by the need to replace the inverse optimization problems with the set of lines and a sharp increase in time complexity. The virtual model method was created. The positive technical effect when using the proposed method in construction was experimentally confirmed. The theoretical foundations of the virtual model method, representing the latter as an imaginary mapping of the object into the environment, impracticable in real conditions of existence were developed. When carrying out calculations on a virtual model in the imaginary environment, followed by a return to the real environment, the method allows significantly (by orders of magnitude) reduce the search time for the optimal solution for CAD systems and ACS. The proposed virtual model method was tested in the environment of the general metrological system «INMER», designed for measurement and control of thermal process parameters during the reinforced concrete hardening in the cold due to processing infrared fluxes from the surface of such products. Within the ACS of the building construction process, «INMER» system was built in as a separate link in the overall automated control system, namely, in the ACS feedback loop. In particular, the «INMER» system tests were carried out at the construction site of "Stikon" Ltd (Odessa). As a result of the tests, increase in the strength of reinforced concrete building products (columns, diaphragms, floor slabs) by 16–19 % was observed.